No causal relationship between serum vitamin D levels and alcoholic liver disease: a two-sample bidirectional Mendelian randomization study - Wu, Huan; Wu, Long; Zhang, Quan; Li, Can; Li, Hai-yang; Zhang, Bao-fang (Frontiers in Nutrition, 2024)
Background: Numerous observational studies have presented an association between Vitamin D (VD) and Alcoholic Liver Disease (ALD). However, sufficient evidence from Randomized Controlled Trials (RCTs) substantiating this correlation is scarce, thus leaving the causality of this relationship ambiguous. To overcome the shortcomings of traditional observational studies, we performed a two-sample bidirectional Mendelian randomization (MR) analysis to ascertain the causal relationship between VD and ALD.We utilized summary statistics datasets from Genome-Wide Association Studies (GWAS) for VD and ALD. We selected genetic instruments that measure circulating VD levels (n=64979), and retrieved ALD statistics from GWASs, inclusive of 1416 cases and 217376 healthy controls, while excluding chronic liver diseases such as nonalcoholic fatty liver disease, toxic liver disease, and viral hepatitis. Subsequent, MR analyses were performed to obtain effect estimates using inverse variance weighted (IVW) random effect models. Cochran' s Q statistic and MR-Egger regression intercept analyses were used to assess pleiotropy. Sensitivity analyses using the MR Egger, weighted median, simple mode, and weighted mode methods were also performed. Leave-one-out analysis was used to identify SNPs with potential effect. Reverse MR analysis was also performed.In IVW, our MR analysis incorporated 21 independent SNPs, circulating VD levels had no causal effect on ALD [OR = 0.624 (0.336-1.160), P = 0.136] and ALD had no causal effect on circulating VD [OR = 0.997 (0.986-1.008), P = 0.555]. No heterogeneity or pleiotropy was observed (P > 0.05). Other MR methods also agreed with IVW results.This study provides the causal relationship between genetically predicted circulating Vitamin D levels and ALD and provides new insights into the genetics of ALD.